(untitled) (Boletín de Investigaciones Marinas y Costeras, 2016)
This is the first report of Enoplometopus antillensis from the Caribbean coast of Colombia. Eleven specimens were collected between 10 m and 25 m of depth. The morphology of the external reproductive structures were described and illustrated.